Insect Atlas as a Learning Resource for Diversity of Insect - Yulianti, Eka; Ni’mah, Zumrotun; Nursin, Lili Shafdila (Proceeding International Conference on Science and Engineering, 2019)
Diversity of insect is a biological theme that allows direct knowledge and experience of learning for student. The author describes 24 order and 34 species of JAZ (Jogja Adventure Zone), Candi Abang, and Liwa Lampung Barat. The research on insect as a source of learning is rarely done. Learning resources in the form of insect diversity atlases can help students to understand insects completely. The author develops a colorful atlas of an insect order using Corel Draw X5 software through the identification o f indicator to be achieved, preparation of materials, layout design, and product printing. the product was assessed by 1 material expert, 1 media expert, 3 peer reviewer, 2 biology teachers and tested by 15 high school/MA students using checklist questionnaire. The result of the overall assessment of the colored atlas of the insect’s diversity showed very good qualifications with an assessment percentage 88,9% and the response of students showed very good qualifications with a percentage 91,2%.